Kepuasan Mahasiswa terhadap Kualitas Pengajaran Dosen, Materi Perkuliahan, Fasilitas Dan Media, Serta Iklim Perkuliahan di Program Studi PGMI Semester V - Yudianto, Asep; Annisah, Siti; Apriyanto, Ridwan Eko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This research is motivated by the importance of learning quality in creating an optimal learning experience in higher education. The identified problem is the variation in student satisfaction levels with lecturers' teaching, course materials, facilities and media, and the learning climate. The purpose of this study is to evaluate the level of satisfaction of fifth-semester students of the PGMI Study Program with respect to these four aspects. This study uses a quantitative descriptive method with data collection techniques through a questionnaire that includes indicators of teaching effectiveness, material relevance, facility availability, and a comfortable learning climate. Data were analyzed using descriptive statistics. The results show that students are generally satisfied with lecturers' teaching (75.7%), course materials (78.5%), and the learning climate (78.6%), although there is still a need to develop interactive teaching methods, apply more practical materials, and improve technology-based facilities. In conclusion, the quality of learning in the PGMI Study Program is adequate, but needs to be strengthened in the aspects of methods, applicable materials, technological facilities, and an inclusive learning climate. This study recommends the need for continuous innovation in learning strategies, improved facility support, and the creation of a more conducive academic environment to further increase student satisfaction.